Tactical Security as a Component of National Security and Comprehensive Defense under the Conditions of Conventional and Hybrid Warfare - Karamyshev, Dmytro; Hordiienko, Liudmyla (Theory and Practice of Public Administration, 2023)
The article examines the essence and peculiarities of the concept of tactical security as a component of national security and comprehensive defense of Ukraine under the conditions of conventional and hybrid warfare, the definition of basic conditions, principles and methodological approaches to the implementation of tactical security measures, the use of appropriate methods and means aimed at increasing the effectiveness of protection population under the influence of conventional and hybrid threats, personal, group and collective security of Ukrainian citizens. The analysis of such components of national security as “state security”, “military security”, “public security” and “individual security” was carried out. It is proposed to introduce the concept of “tactical security” into scientific circulation, taking into account its characteristic features and levels of support.It is emphasized that in the conditions of both conventional and hybrid warfare, unfortunately, the most vulnerable is the problem of ensuring human security, which is the result of unpredictable consequences of both overt and covert military aggression, mainly in the territories that have found themselves and are in the conditions of hostilities and temporary occupation. Attention is focused on the fact that the specified problem is intensifying and requires the development of a complex of urgent, in particular, tactical measures for its regulation with the help of both existing resource capabilities and potential, including innovative technologies, methods and means, and by combining public awareness, state regulatory mechanisms, public-private partnership, civil-military interaction and public activity and participation at the expense of proactive public structures and knowledgeable citizens, including on the basis of international experience in countering hybrid threats.It was determined that tactical security is an integrated concept that is simultaneously derived from military security, public security and individual personal security and, accordingly, can have three main meaningful components: military (component of military security), civil (component of public security and personal security) , as well as integrated, which is reflected in the concept of civil-military interaction to ensure tactical security in the conditions of hybrid warfare. It is caused by the permanent potential and sudden action of various factors, threats and influences, especially those that are difficult to predict in the conditions of both conventional and hybrid war and is aimed at quick prevention and urgent response to these factors, which involves a complex of actions: personal, group, collective and the use of appropriate means of individual, group and collective protection, assistance and care aimed at eliminating life-threatening conditions and their consequences.It has been noted that an important component of planning measures for the implementation of the National Security Strategy of Ukraine is the spread of a public culture of security, a clear understanding of the perspective model of the organization and provision of tactical security, delineation of its levels and types for certain categories of the population, employees and proactive citizens. The implementation of tactical security measures will contribute to ensuring an adequate level of military, public and personal human security and increasing the protection of the population from emergency situations and other dangerous events, as well as dangers arising during or as a result of both armed and covert conflicts in conditions of both conventional and and hybrid warfare.It was concluded that tactical security is an integrated type of security that is in the sphere of relations between the civil and military sectors, which in the future can be transformed into the concept of civil-military cooperation in preventing and responding to various emergency situations and dangerous events, establishing effective cooperation between civil and military structures and during the performance of tasks related to ensuring national security and comprehensive defense under the conditions of conventional and hybrid warfare.